Toni Morrison's fiction - Furman, Jan (Understanding contemporary American literature., 2014)
In this revised introduction to Nobel Laureate Toni Morrison's novels, Jan Furman extends and updates her critical commentary. New chapters on four novels following the publication of Jazz in 1992 continue Furman's explorations of Morrison's themes and narrative strategies. In all Furman surveys ten works that include the trilogy novels, a short story, and a book of criticism to identify Morrison's recurrent concern with the destructive tensions that define human experience: the clash of gender and authority, the individual and community, race and national identity, culture and authenticity, and the self and other.